Spatial and temporal variation in the recruitment of the intertidal barnacles Chthamalus montagui Southward and Chthamalus stellatus (Poli) (Crustacea: Cirripedia) over an European scale. - O´Riordan, R. M. (2009)
Spatial and temporal variation in the recruitment of the intertidal barnacles Chthamalus montagui Southward and Chthamalus stellatus (Poli) (Crustacea: Cirripedia) over an European scale.